Paradoxical Signaling Pathways in Developing Thymocytes - Aws Alshamsan (Frontiers Media S.A., 2011)
ABSTRACT- Thymocytes are subjected to processes of selection during their life in the thymus; negative selection for autoreactive thymocytes and positive selection for self-MHC restricted self-tolerant cells. Interestingly, signals for positive or negative selection originate from the same receptor. More importantly, evidence showed that both death and survival signals are mediated by the MAPK pathway. The degree and order of ERK activation, but not other MAPK proteins, has been found to be different in either cases of cell fate. Therefore, it is suspected that the kinetics of ERK after activation may dictate cell death or survival. There are two important GEF proteins that are involved in Ras/ERK activation, RasGRP and SOS. It is thought that the level, order and kinetics of ERK are influenced upstream by the type of GEF. This review discusses the role of both GEF proteins in positive and negative selection and how this reflects on ERK activation. This article is open POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.